Development of integrated vector algebra e-book islamic values and local culture - Pratiwi, Dona Dinda; Dewi, Novian Riskiana; Kuswanto, Cahniyo Wijaya; Wulandari, Dewi (Universitas Islam Negeri Raden Intan Lampung, 2023)
In proving a theory or mathematical concept, students experience many difficulties in this regard. So we need teaching materials that can support the learning process of students in overcoming this. The purpose of this study was to develop an integrated vector algebra e-book of Islamic values and local culture (Lampung). With this e-book, the learning process does not only carry mathematics education but also Islamic and cultural values. So that students can get to know local culture more closely, giving them more character and quality. Data collection techniques in this study were observation, Product Validation Instruments, Student Response Instruments, and Product Test Documentation. The results showed that an average of 85% was obtained with the attractiveness test criteria achieved, namely